Uncertainty and Campaigns: The Psychological Mechanism Behind Campaign-Induced Priming. (January 2015) - Peterson, David A. M.
Campaigns change how some people vote. How campaigns have this effect is less well understood. The prevailing view is that these effects occur by changing the content of voters' attitudes such as partisanship or issue positions (persuasion) and by changing the weights voters applied to these determinants of vote choice (priming). Recent research has challenged this view and suggests that the support for these priming and persuasion effects is overstated. Unfortunately, no research directly specifies and tests the specific psychological mechanism responsible for campaign priming. In this article, I draw on the differences in the forms of attitude strength and demonstrate that changes in citizens' uncertainty are responsible for these effects. The results suggest that persuasion and changes in uncertainty (but not ambivalence or importance) are responsible for the changes in voters' decisions during the campaign. Substantively, the largest effects occur because of changes in the uncertainty voters have about the nature of the candidates' character traits.